EVALUASI PROTEINURIA PADA PASIEN DIABETES MELITUS DENGAN KEBIASAAN MINUM TEH - Handayani, Trimar; Himawan, Fathurrozak; Prihandana, Sadar (Prodi Keperawatan Tegal Program Diploma III Poltekkes Kemenkes Semarang, 2025)
Diabetes Mellitus (DM) is a chronic metabolic disease that may lead to microvascular complication, including diabetic nephropathy, which is characterized by proteinuria. Proteinuria serves as an early indicatot of kidney damage in DM patients. Tea consumption patterns, particularly green and black tea, have attracted attention due to their polyphenol content, which may provide protective effects on kidney function. This study aimed to evaluate proteinuria status among diabetic patient with daily tea consumption habits. A descriptive cross sectional design was conducted on 51 DM patient at Bandung Primary Health Center, Tegal City (June-July 2025) who had been diagnosed with DM for at least five years, had a habit of drinking tea, and had no history of kidney stones. Data were collected using a questionnaire on respondents’ characteristics and tea consumption habits, followed by urine protein examination. Data analysis was performed descrivtively using frequency distribution. The results shows that the mean age of responden was 58,2 years, with the majority being female (68,6%) and having lived with DM for 5-9 years ( 60,8%). Black tea was the most frequently consumed type (86,7%), with more than five years consumption (84,3%) and two cups per day (41,2%) Proteinuria examination revealed 62,7% negative, 23,5% positive 1, 5,9% positive 2, and 7,3% positive 3. The majority of patients with long-term tea consumption had negative proteinuria results, indicating potensial protective effects on kidney function. However, the presence of 37,3% positive proteinuria suggest that other factors such as glycemic control, duration of diabetes, and variations in the type and intake may still influence the outcomes.